Incidence of HIV-infected infants born to HIV- infected mothers with prophylactic therapy: Preliminary report of hospital birth cohort study - Nia Kurniati; T Nilamsari; Arwin AP Akib (Indonesian Pediatric Society, 2006)
Background Human immunodeficiency virus (HIV) is expandingrapidly and was reported double in several places in Indonesia Toour knowledge, reports regarding HIV-infected infants are stillscarce.Objectives To investigate the incidence of HIV-infected infantsborn to HIV- mothers who had received prophylaxis therapy at birth.Methods A prospective hospital-based cohort study was held fromJanuary 2003 until December 2004 in Cipto Mangunkusumo Hos-pital, Jakarta. The inclusion criteria were mothers with positive HIVand their infants had been given anti retroviral (ARV) therapy. Thebabies were followed up monthly and the status of infection wasdetermined by PCR at the age of 4 weeks and 6 months. Outcomewas measured based on PCR assays or clinical signs of HIV in-fection.Results The mothers’ age ranged from 19 to 27 years. All of themwere carrying their first child and only 41% mothers took ARV pro-phylaxis. Almost all mothers underwent caesarean section and theinfants had formula feeding. HIV infection was diagnosed in 7 in-fants and 2 of them had RNA assays more than 5,000 copies/ml.Six infants were negatives whereas 3 infants were diagnosed asindeterminate HIV infection and needed further examination. Oneneeded no further investigation as the mother was seronegative.Conclusions Preventing HIV transmission from mother to infantcan be done by giving ARV during prenatal, intrapartum, and post-natal period to the newborn. In our hospital, transmission was con-firmed in 6 of 17 infants. Unison protocol must be used and popu-lation of HIV-pregnant mother must be registered in order to knowhow high the transmission rate among Indonesian HIV people